Inhibition of S-Adenosylhomocysteine Hydrolase Induces Endothelial Dysfunction via Epigenetic Regulation of p66shc-Mediated Oxidative Stress Pathway. Issue 19 (7th May 2019) - Xiao, Yunjun; Xia, Junjie; Cheng, Jinquan; Huang, Haiyan; Zhou, Yani; Yang, Xifei; Su, Xuefen; Ke, Yuebin; Ling, Wenhua
Abstract : Background: Elevated levels of S-adenosylhomocysteine (SAH), the precursor of homocysteine, are positively associated with the risk of cardiovascular disease and with the development and progression of atherosclerosis. However, the role of SAH in endothelial dysfunction is unclear. Methods: Apolipoprotein E–deficient ( apoE −/ − ) mice received dietary supplementation with the SAH hydrolase (SAHH) inhibitor adenosine dialdehyde or were intravenously injected with a retrovirus expressing SAHH shRNA. These 2 approaches, along with the heterozygous SAHH gene knockout ( SAHH +/− ) mouse model, were used to elevate plasma SAH levels and to examine the role of SAH in aortic endothelial dysfunction. The relationship between plasma SAH levels and endothelial dysfunction was also investigated in human patients with coronary artery disease and healthy control subjects. Results: Plasma SAH levels were increased in SAHH +/− mice and in apoE −/ − mice after dietary administration of adenosine dialdehyde or intravenous injection with SAHH shRNA. SAHH +/− mice or apoE −/ − mice with SAHH inhibition showed impaired endothelium-dependent vascular relaxation and decreased nitric oxide bioavailability after treatment with acetylcholine; this was completely abolished by the administration of the endothelial nitric oxide synthase inhibitor N G -nitro-L-arginine methyl ester. Furthermore, SAHH inhibition induced production of reactive oxygen species and p66shc expression in the mouse aorta and human aortic endothelial cells. Antioxidants and p66shc siRNA prevented SAHH inhibition–induced generation of reactive oxygen species and attenuated the impaired endothelial vasomotor responses in high-SAH mice. Moreover, inhibition of SAHH induced hypomethylation in the p66shc gene promoter and inhibited expression of DNA methyltransferase 1. Overexpression of DNA methyltransferase 1, induced by transduction of an adenovirus, was sufficient to abrogate SAHH inhibition–induced upregulation of p66shc expression. Finally, plasma SAH levels were inversely associated with flow-mediated dilation and hypomethylation of the p66shc gene promoter and positively associated with oxidative stress levels in patients with coronary artery disease and healthy control subjects. Conclusions: Our findings indicate that inhibition of SAHH results in elevated plasma SAH levels and induces endothelial dysfunction via epigenetic upregulation of the p66shc-mediated oxidative stress pathway. Our study provides novel molecular insight into mechanisms of SAH-associated endothelial injury that may contribute to the development of atherosclerosis. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03345927. Abstract : Supplemental Digital Content is available in the text.